The Tax Cuts and Jobs Act and the Middle Class - Deborah Combs; Brian Nichols (STIE Malangkucecwara, 2019)
This paper explores how the tax cuts and jobs act of 2017 impacts middle-class taxpayers by calculating the tax liability at different levels of income and deductions in 2017 versus 2018. The results confirm the statements supporting the positive effect of the tax change for the middle class. The tax cut and jobs act eliminates personal exemptions, changes the standard deductions at various incomes and family sizes, and lowers marginal tax rates. After providing details of the act, this research examines the definition of the U.S. middle class by using prior research from the Pew Research Center, the United States Census Bureau, and the federal reserve to determine which income levels are attributable to the middle class. Then the tax liability for these income classes is calculated for single and married filing jointly taxpayers in both 2017 and 2018 to determine if the tax cuts and jobs act reduces the tax liability for the middle class. The results show that in almost all scenarios the tax liability in 2018 will be lower than in 2017, regardless of whether standard or itemized deductions are taken. The marriage penalty is no longer applicable, and the new tax act provides a substantial benefit to large families